Perception of Cats: Assessing the Differences Between Videos and Still Pictures on Adoptability and Associated Characteristics - Schoenfeld-Tacher, Regina; Kogan, Lori R.; Carney, Patrick C. (Frontiers in Veterinary Science, 2019)
While animal shelters have made significant progress in reducing the number of euthanized dogs and cats, millions of unclaimed pets are still euthanized every year. Cats, in particular, face bleak prospects, with approximately 70% of those that enter animal shelters euthanized. Many factors influence potential cat adopters’ decisions including a cat’s physical appearance and perceived personality. To explore elements related to the perception of cat personality, this study examined whether videos and pictures highlight different characteristics felt to potentially affect perceived cat adoptability. An online survey was used to assess perceptions regarding videos and pictures of cats. The survey consisted of three adult cats viewed in a short video and as a still picture. Participants were asked to view the media and rate how well these images depicted 12 separate characteristics (from extremely well to not well at all). Respondents were then asked how likely they would be to adopt this cat if they “were in the market to adopt a cat”. A total of 555 surveys were analyzed to answer two questions. The first question was whether cats were perceived as more adoptable when viewed in a still photo or in an action video. A statistically significant difference was found between median photo and video adoption scores for all three cats, with video scores consistently higher than photo scores. The other question was how video footage might alter perception of cats when compared to still photos. For all three cats, the traits “Playful,” “Aggressive,” “Active,” and “Curious” received higher scores when the cats were viewed in videos vs. photos. All of these traits can be associated with active behaviors, best demonstrated via motion. The cats, however, were seen as more “Loving,” “Shy,” “Quiet,” and “Likes to be held” in photos compared to videos. The results suggest that there is an advantage of videos over pictures in perceived adoptability, as determined by response to the question “how likely would you be to adopt this cat”, but this difference is small and likely does not justify additional resources. Exceptions might be for active, outgoing cats in order to highlight these attributes.